PID Controller for Batch Process using MATLAB-Simulink-Real-Time-Windows Target - N., Aziz; S., Abdul Sata; S.A., Zulkeflee
The difficulties in implementing a controller in the real process leads to the practice of a real-time user-friendly simulator programming. This paper presents the application of the Simulink model as a Graphical User Interface (GUI) for signal visualization and parameter tuning in the real-time implementations.